The Sociology of Healthcare Safety and Quality 2016
DOI: 10.1002/9781119276371.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Enacting Corporate Governance of Healthcare Safety and Quality: A Dramaturgy of Hospital Boards in England

Abstract: The governance of patient safety is a challenging concern for all health systems.Yet, while the role of executive boards receives increased scrutiny, the area remains theoretically and methodologically underdeveloped. Specifically, we lack a detailed understanding of the performative aspects at play: what board members say and do to discharge their accountabilities for patient safety. This article draws on qualitative data from overt non-participant observation of four NHS hospital Foundation Trust boards in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…This systematic review identified evidence for 8 hospital-based interventions targeting high-risk patient populations: discharge planning, 20,37,38,43,46 geriatric assessment or consultation, 33,39,44,47,49 medication management, 31,34,45 clinical pathways, 36,42 interdisciplinary or multidisciplinary care, 40,48 case management, 35 hospitalist services, 41 and telehealth. 32 As shown Table 3 Hospitalized older patients often have increased costs, complications, worse outcomes, 53,54 and longer LOS compared with younger patients. For example, a study by Freeman et al 53…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review identified evidence for 8 hospital-based interventions targeting high-risk patient populations: discharge planning, 20,37,38,43,46 geriatric assessment or consultation, 33,39,44,47,49 medication management, 31,34,45 clinical pathways, 36,42 interdisciplinary or multidisciplinary care, 40,48 case management, 35 hospitalist services, 41 and telehealth. 32 As shown Table 3 Hospitalized older patients often have increased costs, complications, worse outcomes, 53,54 and longer LOS compared with younger patients. For example, a study by Freeman et al 53…”
Section: Discussionmentioning
confidence: 99%
“…32 As shown Table 3 Hospitalized older patients often have increased costs, complications, worse outcomes, 53,54 and longer LOS compared with younger patients. For example, a study by Freeman et al 53…”
Section: Discussionmentioning
confidence: 99%
“…Finally, performative and symbolic framings focus on the importance of the symbolic and ceremonial value of Boards, and explore Board performances in a dramaturgical sense (Freeman et al., 2016). Such approaches are based on the assumption that Boards undertake important conditioning work outside of formal Board meetings.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention, Summary Health Statistics: National Health Interview Survey, 2016 reported that over 36 million people are treated in hospitals across the United States (U.S.) annually [2]. These healthcare organizations are environments where people interact with healthcare experts to achieve healing, health, and wellbeing.…”
Section: Introductionmentioning
confidence: 99%